Action Theoretical Implications for Innovativeness: A Concept for School Education? - Scharf, Claudia; Gryl, Inga (Momentum Quarterly, 2021)
Facing current societal challenges, an education is needed which enables students to participate in society. At the same time, contrary to a humanistic education for maturity, education is scarred by neoliberal practice; manifested in efficiency and achievement orientation. Countering those practices, the concept innovativeness aims at enabling pupils to participate in society – with a focus on reflexivity, creativity and implementivity as well as innovation processes; implying reflections on theoretical and practical ethics. In order to set the basis for a didactic implementation of an approach which aims at enabling to act, an action theory foundation of innovativeness is needed. This paper intends to set this foundation by the use of Habermas’ Theory of Communicative Action und Joas’ Creativity of Action – theories, which address on the one hand the discursive argumentation of validity claims and on the other hand the dynamic of shaping (or rather innovation) processes.